2009
DOI: 10.3858/emm.2009.41.9.072
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin inhibits cellular condensation and alters microfilament organization during chondrogenic differentiation of limb bud mesenchymal cells

Abstract: Curcumin is a well known natural polyphenol product isolated from the rhizome of the plant Curcuma longa, anti-inflammatory agent for arthritis by inhibiting synthesis of inflammatory prostaglandins. However, the mechanisms by which curcumin regulates the functions of chondroprogenitor, such as proliferation, precartilage condensation, cytoskeletal organization or overall chondrogenic behavior, are largely unknown. In the present report, we investigated the effects and signaling mechanism of curcumin on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…We found that CUR suppresses FAK phosphorylation sites at Tyr397, 407, 576, 577, 861, and 925 in HCT-116 cells; result is partly consistent with other studies where it has been reported that CUR inhibits cell growth and migration through FAK activities [41]. CUR abrogates the chondrogenesis by downregulation of integrins and FAK leading to cytoskeleton remodeling by Akt signals [42]. CUR prevents mouse-rat hybrid retina ganglion cell migration and invasion via abrogation of FAK MMP-2, MMP-9, Rho-A, and ROCK gene expressions [29].…”
Section: Discussionsupporting
confidence: 90%
“…We found that CUR suppresses FAK phosphorylation sites at Tyr397, 407, 576, 577, 861, and 925 in HCT-116 cells; result is partly consistent with other studies where it has been reported that CUR inhibits cell growth and migration through FAK activities [41]. CUR abrogates the chondrogenesis by downregulation of integrins and FAK leading to cytoskeleton remodeling by Akt signals [42]. CUR prevents mouse-rat hybrid retina ganglion cell migration and invasion via abrogation of FAK MMP-2, MMP-9, Rho-A, and ROCK gene expressions [29].…”
Section: Discussionsupporting
confidence: 90%
“…23 The early and extensive cell-cell interaction in the PLCL/chitosan was followed by subsequent reorganization of actin cytoskeletal to the cortical with a concomitant rounding of cells forming cell aggregation, an event reported to associate with the activation of stem cells chondrogenic differentiation. [24][25][26] Taken together, our data indicate that provision of the scaffold surface with chitosan coating greatly enhanced MSC distribution in the scaffold. The strikingly different morphology acquired by the MSCs on attachment to the two scaffolds might have a direct effect on subsequent differentiation.…”
Section: Discussionsupporting
confidence: 55%
“…We chose this concentration based on previous studies in our laboratory demonstrating that canine MSCs do not tolerate curcumin concentrations higher than 5 ÎŒM. A recent study by Kim and co-workers demonstrated that chick MSCs treated with 20 ÎŒM curcumin become apoptotic and do not undergo chondrogenesis [ 39 ]. This clearly demonstrates that MSCs can only tolerate lower concentrations of curcumin in contrast to chondrocytes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%